Is resilience related to help-seeking behavior? A study on family caregivers of people with mental illness - Andi Buanasari; Asep Rahman; Lenny Gannika (University of Muhammadiyah Malang, 2023)
Introduction: Caring for family members with mental illness can be challenging and cause a burden of caring. Family caregivers need to adapt to challenging caring tasks by having good resilience that leads to positive help-seeking behavior. Objectives: This study aims to investigate the correlation between resilience and help-seeking behavior among Family Caregivers who care for people with mental illness in Manado City. Methods: This study is a cross-sectional study involving 84 family caregivers of people with mental illness. The data was collected using the Walsh Family Resilience Questionnaire (WFR-Q) to measure family caregiver resilience and the Attitudes Toward Seeking Professional Psychological Help (ATSPPH-SF) to measure help-seeking behavior. Data analysis was performed using Pearson correlation to analyze both variables’ strengths and direction. Results: This study reported that there was a positive and moderate correlation between resilience and help-seeking behavior among family caregivers of people with mental illness (p = 0.000 r = 0.496), The majority of respondents have cared for people with mental illness for more than five years, and most of them are the children of People with mental illness. Conclusions: These results indicated the importance of resilience and positive help-seeking behavior among Family Caregivers because they influence each other. Programs to strengthen the resilience of family caregivers need to be carried out to improve their caring ability by strengthening positive help-seeking behavior.